The eigenvalue for a class of singular p-laplacian fractional differential equations involving the Riemann-Stieltjes integral boundary condition - Zhang, Xinguang; Liu, L.; Wiwatanapataphee, B.; Wu, Yong Hong (Elsevier Inc., 2014)
In this paper, we are concerned with the eigenvalue problem of a class of singular p-Laplacian fractional differential equations involving the Riemann–Stieltjes integral boundary condition. The conditions for the existence of at least one positive solution is established together with the estimates of the lower and upper bounds of the solution at any instant of time. Our results are derived based on the method of upper and lower solutions and the Schauder fixed point theorem.